ICE Tourism / Shaiful Azli Muhamad Surol, E & L Event and Ezwani Azmi - Muhamad Surol, Shaiful Azli; Event, E & L; Azmi, Ezwani (Division of Research and Industry Linkages, 2017)
"ICE Tourism project is a combination of several categories in tourism themes which suitable for adaptation and carrying benefits to the community, as well as economic development for rural areas. Word of 'ICE' is a brand of this project where the features of ice cubes; cool, attractive, relief and fragile illustrated the objective of this project in realizing innovation for the development of rural area throughout Malaysia. The idea of ICE Tourism came from the tourism themes which consists of ISLAMIC tourism, CREATIVE Tourism & EDULOGY Tourism (Education = Education & Ecology = Nature) as a core of travel package criteria to be produced with involvement of various parties and agencies. The concept of ICE Tourism is also emphasizing future INNOVATION, COLLABORATION & ENVIRONMENT with the ability to produce diversity of rural areas potentials to generate income, contribution towards local economy, promoting social activities, natural conservation/awareness and the combination of various parties through cooperation and collaboration to ensure conformity and the area branding. This project provides a space and opportunity to generate income based on the respective expertise. ICE Tourism concept will also highlight the symbolic significance to the symbiosis relationships of God, Human and Nature.